The Science of the Soul : The Commentary Tradition on Aristotle's De anima, c. 1260-c. 1360 - Boer, Sander Wopke de (Book collections on Project MUSE., 2013)
The transformation of the science of the soul between 1260 and 1360Aristotle''s highly influential work on the soul, entitled De anima, formed part of the core curriculum of medieval universities and was discussed intensively. It covers a range of topics in philosophical psychology, such as the relationship between mind and body and the nature of abstract thought. However, there is a key difference in scope between the socalled 'science of the soul'', based on Aristotle, and modern philosophical psychology. This book starts from a basic premise accepted by all medieval commentators, namely that.